Revoicing Intangible Cultural Heritage: Perspectives from the Margins of Europe - Hodsdon, Laura; Ernstreits, Valts; Koreinik, Kadri; Moenandar, Sjoerd-Jeroen (Critical Heritages of Europe, 2025)
Revoicing Intangible Cultural Heritage draws upon an original, wide-ranging dataset to show that the dynamics and ethics of participation in European national minority cultures' intangible cultural heritage (ICH) are more nuanced than has previously been articulated. Arguing for an approach to analysing ICH that reflects societal change in regions that are historically those of national minorities, contributions to the volume focus on three regions across four countries. This allows for comparative exploration of exemplar contexts that span a range of circumstances in which European national minority cultures thrive and strive for voice and recognition. It explores how a wide range of people engage with national minorities' ICH and seeks a better understanding of the ethical and practical dimensions of this participation. It proposes a heritage literate 'revoicing' of ICH: to create socially positive pathways to resilient ICH, and in turn ensure ICH is an arena where these positive social relations are shaped as part of an evolving ecosystem into the future. Revoicing Intangible Cultural Heritage takes an interdisciplinary approach ideally placed to interrogate the interplay of different groups with ICH from multiple perspectives. This makes the book essential reading for academics and students working in heritage studies, sociolinguistics, cultural and event studies, sociology, creative practice, and cultural geography.